LIGHTWEIGHT CONCRETE MAKING ANALYSIS USING MIXED CELLULOSE - Nanang Budi Setyawan; Fredy Kurniawan (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Development era of globalization has resulted in increasing number of second-hand goods / waste that its existence can be a problem for life in the future. Many things are done in order to recycle paper cement in order to overcome this problem the existence of waste. One way is to use waste paper to be a part of the building. The purpose of this study, to determine the compressive strength and optimum density. Laboratory experimental method uses a variation of 10%, 20%, 30% and testing conducted in the form of compressive strength and density. From the test results obtained by the result of decrease in the compressive strength and density. In addition cellulose concrete mix design with variations determined that 10%, 20%, 30% resulted in a decrease in the compressive strength of concrete,